On the regularity of the pressure field of relaxed solutions to Euler equations with variable density - Precioso, Juliana Conceição [UNESP] (Elsevier, 2014)
In this paper we improve the regularity in time of the gradient of the pressure field in the solution of relaxed version of variational formulation proposed by V. I. Arnold and by Y. Brenier, for the incompressible Euler equations with variable density. We obtain that the pressure field is not only a measure, but a function in Lloc2((0,T);BVloc(D)) as an extension of the work of Ambrosio and Figalli (2008) in [1] to the variable density case. © 2013 Elsevier Ltd.
Keywords: Euler equations; Incompressible flows; Relaxed solutions